Instagram sebagai Media Promosi Utama Radio Mara FM pada Era Digital - Very Vebrio; Maryani, Anne (Bandung Conference Series: Public Relations, 2024)
Abstrack. In this research entitled "Instagram as the Main Promotion Media for Radio Mara FM", the researcher attempts to reveal promotional planning, the promotion process and the urgency of using Instagram as the main promotion media. This research uses a methodology with a constructivist paradigm and qualitative methods as well as a Robert K. Yin case study approach with sub-explanatory. With new media and marketing and promotion theories, this research is able to answer all existing questions. With conclusions such as this promotion planning, Radio Mara FM forms the company's structural framework by dividing fields and mapping human resources. Apart from that, in the promotion planning process, discussions are held to get ideas and ideas regarding promotions on Instagram. So that the person responsible for the program is formed, namely the Project Manager Program. With these three things, it is believed that Radio Mara FM prioritizes the aspect of maximizing human resources compared to promotional content on Instagram. Radio Mara FM tries to process Instagram promotion by making the social media team into content creators whose job is to produce interesting content every day. This content is clearly different from radio products. This is because Instagram promotion is a form of increasing the image and sales of Radio Mara FM. Evaluation is carried out based on feedback and responses from the public and clients. The execution of Instagram promotional publications is carried out by internal content creators at Mara FM Radio. After going through the research process, the researchers concluded that Radio Mara FM uses Instagram as a form of digital existence. Abstrak. Pada penelitian ini yang berjudul “Instagram Sebagai Media Promosi Utama Radio Mara FM”, peneliti berusaha untuk mengungkap perencanaan promosi, proses promosi dan urgensi penggunaan Instagram sebagai media utama promosi. Penelitian ini menggunakan metodologi dengan paradigma konstruktivisme dan metode kualitatif serta pendekatan studi kasus Robert K. Yin dengan sub eksplanatoris. Dengan teori new media dan pemasaran serta promosi, penelitian ini mampu menjawab seluruh pertanyaan yang ada. Dengan kesimpulan seperti perencanaan promosi ini, Radio Mara FM membentuk kerangka struktural perusahaan dengan membagi bidang dan pemetaan sumber daya manusia. Selain itu, pada prosesnya perencanaan promosi dilakukan musyawarah guna mendapatkan ide dan gagasan mengenai promosi pada Instagram. Sehingga terbentuk penanggungjawab program yaitu Project Manager Program. Dengan ketiga hal tersebut diyakini, bahwa Radio Mara FM lebih mengutamakan aspek pemakasimalan sumber daya manusia dibandingkan dengan konten promosi pada Instagram. Radio Mara FM berusaha memproses promosi Instagram dengan cara menjadikan para tim media sosial sebagai content ceator yang bertugas memproduksi konten yang menarik setiap harinya. Konten-konten ini pun jelas berbeda dengan produk radio. Hal ini dikarenakan promosi Instagram sebagai bentuk peningkatan citra dan sales dari Radio Mara FM. Evaluasi dilakukan berdasar kepada feedback dan respon dari publik dan klien. Eksekusi publikasi promosi Instagam dilakukan oleh para content creator Internal Radio Mara FM. Setelah melalui proses riset peneliti menyimpulkan Radio Mara FM menggunakan Instagram sebagai bentuk eksistensi digital.